2014
DOI: 10.1159/000366140
|View full text |Cite
|
Sign up to set email alerts
|

Complete Occlusion of a Subcutaneous Pyelovesical Bypass Graft (Detour® System) Caused by Uric Acid Stone Formation

Abstract: Subcutaneous pyelovesical bypass graft (SPBG) is a urinary diversion treatment option for ureteral obstruction. Initially its use was limited to palliative care patients. However, the indication profile has been extended to selected patients with benign conditions causing ureteral obstruction and hydronephrosis. Occlusion of SPBGs is rarely reported and mostly related to infections. We describe the clinical case of a patient with SPBG after iatrogenic ureteral stricture who was not suitable for other reconstru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…These types of complications are rare and we find few references in the literature [ 10 , 15 ]. Wilhem et al reported an occlusion of the bypass with acid uric lithiasis, insufficiently managed through endoscopic intervention and solved with forced chemolitholysis [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…These types of complications are rare and we find few references in the literature [ 10 , 15 ]. Wilhem et al reported an occlusion of the bypass with acid uric lithiasis, insufficiently managed through endoscopic intervention and solved with forced chemolitholysis [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“… , Wilhelm et al . ). Patients are advised to increase their water intake and intermittently compress the subcutaneous tubing to help prevent obstructions.…”
Section: Nephrovesical Subcutaneous Ureteral Bypass/artificial Uretermentioning
confidence: 97%
“…However, urinary tract infection, Candida species positive urine cultures, fungal ball occlusion, stone occlusion, encrustation and death secondary to fungal infection-induced septic shock have been described in association with the device. (Burgos et al 2009, Gerullis et al 2010, Muller et al 2011, Wilhelm et al 2014. Patients are advised to increase their water intake and intermittently compress the subcutaneous tubing to help prevent obstructions.…”
Section: Nephrovesical Subcutaneous Ureteral Bypass/artificial Uretermentioning
confidence: 99%
“…These encrustations were managed successfully with ureteroscopy and Holmium laser lithotripsy. Previous attempts have failed ureteroscopic management of Detour encrustations 9 . This case demonstrates the feasibility of flexible ureteroscopy and Holmium laser lithotripsy of encrustations since there were no kinks in the Detour device.…”
Section: Cuaj -Spotlight In Urologymentioning
confidence: 99%